Adaptation of porcine reproductive and respiratory syndrome virus to modifications in CD163 - Shadipeni, Naemi (Kansas State University, 2019)
Porcine reproductive and respiratory syndrome (PRRS) is an economically important disease of pigs caused by porcine reproductive and respiratory syndrome virus (PRRSV), a virus endemic to most pork producing countries. CD163, a surface receptor expressed on porcine alveolar macrophages (PAMs) is required for infection. Genetically modified pigs with a complete CD163 knock out are non-permissive for PRRSV infection. CD163 is also involved in the regulation of the innate immune response and the removal of hemoglobin-haptoglobin complexes. Therefore, genetically modified pigs lacking complete CD163 may suffer health consequences. Scavenger receptor cysteine rich domain 5 (SRCR5), one of the nine extracellular domains of CD163, forms the point of interaction between CD163 and PRRSV. Mutations in domain 5 were created by inserting proline-arginine (PR) dipeptides in the SRCR5 genome along the domain 5 polypeptide. Constructs were expressed in HEK cells and infected with PRRSV. Mutations were placed in three groups: 1) infection levels similar to WT-CD163; 2) mutations that produced a severe effect on infection; and 3) mutations that resulted in a moderate reduction of infection. The hypothesis tested in this project is that serially passaging PRRSV on HEK cells expressing modifications on SRCR5 of CD163 will result in adaptation of viruses to the CD163 modifications. Furthermore, adaption will be the result of mutations in PRRSV surface envelope glycoproteins, GP2, GP3 or GP4. To test this hypothesis, PRRSV was repeatedly passaged in cells expressing modifications in CD163. Viral sequences were analyzed for the presence of mutations and viral growth patterns were assessed. After six passages, adaptations to PR-22 and PR-58 mutant CD163 constructs were located in non-surface region of the PRRSV matrix (M) protein. The mutation in PR-22 was a threonine to isoleucine substitution at position 141 (T141I) in the endodomain region. The mutation in PR-58 was a tyrosine to histidine substitution at position 86 (Y86H) in the third transmembrane domain region of M. The results show that mutations in PRRSV occur in response to serial passage on cells expressing modified CD163 proteins; however, mutations were not located in the surface glycoproteins, but in the nonglycosylated M protein.
Keywords: Porcine reproductive and respiratory syndrome virus; CD163